Socio-Religious Issues in the Debate on Masculinity in Yorubaland, Nigeria - Gbenle, Grace Olayinka (NIU Journal of Humanities; Vol 3 No 3 (2018): KIU Journal of Humanities, Vol. 3 No. 3, September 2018, 2018)
The word masculinity is gender related but not limited to it. Masculinity is also related to socio-cultural cum religious values.  From a young age, right through to manhood and beyond, men and boys in Nigeria are measured according to the social construction of masculinity. Fatherâ€™s drill values into their sons under pain of violence and shame for any transgression. From employment, to religious observance, to the style of their hair, boys are trained to be subservient to the masculine ideal; strong, heterosexual and anti-feminine. Thereafter, this paper shall examine the Yoruba culture and her concept of Masculinity and follow it up with various socio cum religious issues that has emerged from her debate on the understanding of masculinity in the Yoruba thought.  In all of these, a quantitative method of research which involve the use of thirty Interview Respondents in all, 5 persons comprising of males and females from each State in South West Nigeria will be interviewed to gather information who will be primarily Yoruba in order to enrich this work. In addition, the experience of the researcher in the past as an indigene of Yoruba will also be of immense contribution to this research as a form of participant observation. I am also going to quote profusely from scholars and leading authorities whose researches, thoughts and opinions have guided our own efforts in this submission. Keywords: Socio-Religious, Masculine debate, Yoruba, Yoruba land, Nigeria